Efektivitas Pemanfaatan Dana Bantuan Operasional Kesehatan untuk Program Kesehatan Ibu dan Anak di Puskesmas Melolo, Kabupaten Sumba Timur - Anggreany Dean R. Manu; Erni E. Pua Upa; Rina Waty Sirait (Media Kesehatan Masyarakat, 2022)
Maternal mortality ratio in East Nusa Tenggara fluctuated from year to year. In 2016 the maternal mortality rate was 131 per 100,000 live births, in 2017 it was 120 per 100,000 live births and in 2018 it was 161 per 100,000 live births. Health efforts are needed to overcome these problems. One of the efforts made is the provision of a Special Allocation Fund (BOK Funds) to improve the quality and access to health services aimed at reducing maternal, infant and child mortality, overcoming nutritional problems, controlling disease and environmental health, especially in areas that have many health problems. The purpose of this study was to determine the effectiveness of the use of BOK funds for the MCH program at Puskesmas Melolo, East Sumba Regency in 2020. This research is a descriptive qualitative research. There were 4 informants in this study, namely the head of the puskesmas, the person in charge/manager of the BOK funds, the KIA coordinator and the person in charge for the health of UKS/youth Data were collected by conducting in-depth interviews and observations and analyzed qualitatively. The results showed that the absorption of BOK funds for the MCH program at the health center reached 80% or Rp180,760,000 from the target of Rp. 225,950,000 that was set at 100%. MCH efforts have been carried out in accordance with the technical guidelines for the use of BOK funds. The use of BOK funds for the MCH program at puskesmas has been effective. It is expected that each program manager will use the funds in accordance with the existing technical guidelines.